Analysis of the performance, emission and combustion characteristics of a turbocharged diesel engine fuelled with Jatropha curcas biodiesel-diesel blends using kernel-based extreme learning machine - Silitonga A.S.; Hassan M.H.; Ong H.C.; Kusumo F. (Springer Verlag, 2023)
accuracy assessment; biofuel; combustion; diesel engine; exhaust emission; industrial emission; machine learning; numerical model; parameter estimation; performance assessment; software; testing method; Jatropha curcas; biofuel; gasoline; analysis; chemistry; exhaust gas; Jatropha; machine learning; Biofuels; Gasoline; Jatropha; Machine Learning; Vehicle Emissions